Du droit comme discours et comme dispositif - Sonia Desmoulin-Canselier (Tracés, 2014)
This paper gives a commentary on a book entitled L’ordre juridique et le discours du droit. Essai sur les limites de la connaissance du droit (The legal order and the legal discourse. Essay on the limits of law understanding) written by a French Professor in Law, Rémy Libchaber (Paris, LGDJ, 2013). It exposes, with inevitably personal viewpoint, some key elements of an original definition of the Law. Trying to propose something different from positivist or naturalist theories and to reconciliate theory and practice, Rémy Libchaber develops the idea of the Law as a discourse and the Legal order as device allowing the production of this discourse. He adds a cultural conception of the Law which opens interesting avenues worth exploring. This presentation leads to critical interrogations. What reveals such a publication about what is going on in French universities of Law ? Does the definition proposed constitute a federative project or a marginal thesis ? Despite of its seduction, some indications lead to seriously doubt the paradigmatic vocation of the new suggested frame for thought.